2009 11th Electronics Packaging Technology Conference 2009
DOI: 10.1109/eptc.2009.5416421
|View full text |Cite
|
Sign up to set email alerts
|

Properties of conductive microstructures containing nano sized silver particles

Abstract: The properties of the structures made by ink-jet printing with the use of the ink containing nano silver sized particles are presented. After structures printing on substrate, to obtain good electrical conductivity, sintering process is necessary. It is shown, that thermal process influences strongly the resistance, and after the process the resistivity of printed structures can be only a little bit higher than the value of the bulk material. Also different electrical test proved similarity between printed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Others have shown that by embedding polymers into the ink will give a more durable structure [52] . The polymers will prevent microcracking of the sintered structure that otherwise occurs due to the burn-off of the solvent [26] .…”
Section: Resultsmentioning
confidence: 99%
“…Others have shown that by embedding polymers into the ink will give a more durable structure [52] . The polymers will prevent microcracking of the sintered structure that otherwise occurs due to the burn-off of the solvent [26] .…”
Section: Resultsmentioning
confidence: 99%
“…Their meandershaped structure is similar to that already presented in other works concerning the fabrication of resistive temperature sensors on flexible substrates [16,17], even though such devices were realized by means of standard microfabrication methods. Silver inkjet-printed line-shaped resistors have already been presented in the literature [18] and, even though not specifically designed as sensors, a characterization of the resistance variation versus temperature was provided; therefore, to the best of our knowledge, we can conclude that there are no previous publications describing meandershaped inkjet-printed/electroplated resistors for temperature sensing. A flexible encapsulation technique based on dry film photoresist rims capped with a micro-porous membrane was developed in order to protect the system and make it more robust and reliable.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of printing techniques to produce the electrical circuits in substrates with the use of metallic nanoparticles inks, has given new possibilities for the electronic market by reducing application material costs, adding new functionalities to existing products, enabling new applications and increasing production yield. Such applications comprise display devices, photovoltaic, lighting, radio-frequency identification (RFID) and other devices [1].…”
Section: Introductionmentioning
confidence: 99%